ANALISIS PENGENDALIAN KUALITAS HASIL PRODUK CETAK KEMASAN DENGAN METODE SIX SIGMA PADA INDUSTRI PERCETAKAN: ANALISIS PENGENDALIAN KUALITAS HASIL PRODUK CETAK KEMASAN DENGAN METODE SIX SIGMA PADA INDUSTRI PERCETAKAN - Vugun Nur Fauzi; Sumarsono; Sulung Rahmawan Wira Ghani; Andhika Mayasari (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
Maintaining high quality is crucial for any company that produces goods. PT. Dharma Anugerah Indah specializes in printing and packaging, but customers have been complaining about the quality of their products in 2022. Specifically, there were many defects in the packaging, particularly problems with the color. These defects have caused a decrease in customer trust and could harm the company's reputation. This study aims to identify the problems causing the defects that are triggering customer complaints. To analyze the defects, we used the Six Sigma method with the DMAIC cycle and the FMEA method. In the define phase, we found that the most significant problems were related to color, bad printing, and bad glueing. These issues were mainly caused by operator negligence, frequent machine trouble, poor materials, and inadequate environmental conditions. However, our Six Sigma calculations show that the Sigma levels were good, ranging from 4.2 to 4.24. We also used the FMEA method to prioritize the failure modes and determine proposed improvements. Based on the proposed improvements, we recommend scheduling work training, monitoring employee performance, maintaining production machines, and increasing awareness of the work environment to improve production quality.